Evaluation of SWAT in Hydrological Modeling and Comparison of Model Accuracy in Using of Daily and Monthly Data, Case Study of Maroon Basin - Mostafa Mirmehdi; Mojtaba Shourian; Ahmad Sharafati (مهندسی منابع آب)
AbstractIntroduction: In recent years, basins hydrological modeling has been one of the important issues, which its results have a significant impact on water resource planning. One of the tools in basins hydrological modeling is SWAT (Soil and Water Assessment Tools), this tool can be used as an extension in GIS software. The purpose of this research is to evaluate the accuracy of SWAT in Maroon basin hydrological modeling.Methods: The calibration and validation of model, used from the flow data measured at the Idenak and Tange-Takab stations in the period of 1991 to 2017.Findings: The results showed that the accuracy of the model in using daily data is lower than monthly data. The reason of the reduction of the accuracy in using of daily data compared to using of monthly data is that the daily calibrated data in each hydro-station is 3450 numbers and for the monthly data is 108 numbers. The simulation results show that the SWAT has an acceptable ability in the basins hydrological simulation with a mountainous nature and the process of flow changes in the calibration and validation stage is simulated with acceptable accuracy.